A view from the other side: A senior's view of participating in online groups during the pandemic. Issue 1 (2nd January 2022) - Saldanha, Kennedy
ABSTRACT: While Covid-19 has taken a heavy toll on the 1.3 million residents in nursing facilities, there are five times the number of elders who live in the community. This story highlights the perspectives and experiences of an active senior in an independent living facility in Toronto who transitioned to online groups during the pandemic. A positive experience in an online group, together with her own resilience and tenacity, introduced her to a whole new world of online groups, enabling her to stay healthy, active, and connected beyond the confines of her studio apartment. As the pandemic and winter leave seniors living in the community indoors for the foreseeable future, there is need to draw attention to online recreational/leisure groups and build capacity for them.